Knowledge Sharing Behavior: The Mediating Role of Psychological Safety in Health Care Units - Ousmane, Hendrik; Doan, Semenyo (Yayasan Gema Bina Nusantara, 2025)
In the high-pressure environment of modern healthcare, the ability to exchange critical information, clinical insights, and experiential wisdom is a fundamental determinant of patient safety and organizational resilience. Knowledge Sharing Behavior (KSB) within health care units is not merely a professional courtesy but a life-saving necessity. However, the hierarchical nature of medical institutions and the high stakes of clinical errors often create an atmosphere of silence, where staff members hesitate to share “half-baked” ideas or report “near-miss” incidents. This research investigates the mechanisms for nurturing KSB by focusing on the pivotal mediating role of Psychological Safety. Drawing upon Social Cognitive Theory and Social Exchange Theory, this study examines how organizational antecedents specifically inclusive leadership and organizational trust influence the willingness of healthcare professionals to engage in knowledge donating and collecting. A quantitative research design was employed, utilizing a structured survey administered to 400 healthcare practitioners, including doctors, nurses, and allied health professionals across various specialized units. Data were analyzed using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach to test the hypothesized mediating pathways. The empirical findings reveal that Psychological Safety acts as a potent mediator; while structural support and trust are necessary, they are insufficient to trigger consistent knowledge sharing unless staff members feel interpersonally safe to take risks. The results indicate that in units characterized by high psychological safety, there is a significantly higher frequency of informal knowledge exchange and collaborative problem-solving. This study contributes to healthcare management literature by highlighting that the path to a